Journalistic performance in Latin America: A comparative study of professional roles in news content. (October 2017) - Mellado, Claudia; Márquez-Ramírez, Mireya; Mick, Jacques; Oller Alonso, Martín; Olivera, Dasniel
Comparative research across the world has shown that nation-level variables are strong predictors of professional roles in journalism. There is, however, still insufficient comparative research about three key issues: cross-national comparison of journalistic role performance, exploration of how – or whether – organizational variables account for variation in role performance across countries, and the performance of specific journalistic roles that prevail in regions with post-authoritarian political trajectories. This article tackles these three issues by comparatively measuring journalistic performance in five Latin American countries. Based on a content analysis of 9841 news items from 18 newspapers, this article reports findings from Brazil, Chile, Cuba, Ecuador and Mexico, by analyzing the presence of the 'interventionist', 'watchdog', 'loyal', 'service', 'infotainment', and 'civic' roles. Results show that the region is far from homogeneous and that while 'country' is a strong predictor for most of the roles, other variables such as 'media type', 'political orientation', and 'news topic' are also significant predictors to varying levels.